MODEL OF INCREASING MSME COMPETITIVENESS IN TEBING TINGGI CITY IN THE DIGITAL REVOLUTION ERA - Gunawan, Didik; Hartanto, Bobby (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine the Model of Increasing the Competitiveness of MSMEs in the City of Tebing Tinggi in the Era of the Digital Revolution. The population of this research is MSME customers in Tebing Tinggi City with a sample of 96 respondents. Methods of data analysis using SmartPLS 3.0 with the results: halal labels, Electronic Word of Mouth and Product Quality partially affect the Brand Image of MSME customers in Tebing Tinggi City. Halal label, Electronic Word Of Mouth and Product Quality partially affect Brand Trust for MSME customers in Tebing Tinggi City. Halal label, Electronic Word Of Mouth and Product Quality have no partial effect on purchasing decisions for MSME customers in Tebing Tinggi City. Brand Image and Brand Trust have a partial effect on purchasing decisions for MSME customers in Tebing Tinggi City. Brand Image can mediate the effect of halal label and Electronic Word Of Mouth on Purchase Decision, but not on the influence of Product Quality on Purchase Decision. The same thing happened to Brand Trust.